Constantine Warner Bros Pictures ; in association with Village Roadshow Pictures a Donner's Company, Batfilm Productions, Weed Road Pictures, 3 Arts Entertainment production ; directed by Francis Lawrence ; edited by Wayne Wahrman. - Lawrence, Francis.; Reeves, Keanu, 1964-; Wahrman, Wayne.; Weisz, Rachel, 1971- (Warner Bros Pictures, 2005)
Basado en los personajes de Hellblazer de DC Comics/Vertigo. Constantino cuenta la historia de un detective supernatural irreverente John Constantine (Keanu Reeves), que ha estado literalmente en el infierno y en el mundo de los vivos.